Ammonium induced dysfunction of 5-HT2B receptor in astrocytes. (October 2019) - Yue, Tingting; Li, Baoman; Gu, Li; Huang, Jingyang; Verkhratsky, Alexei; Peng, Liang
Abstract: Previously we reported that gene expression of astrocytic 5-HT2B receptors was decreased in brains of depressed animals exposed to chronic mild stress (CMS) (Li et al., 2012) and of Parkinson's disease (Song et al., 2018). Depression is also one of the psychiatric symptoms in hyperammonemia, and astrocyte is a primary target of ammonium in brain in vivo . In the present study, we have used preparations of the brains of urease-treated mice and ammonium-treated astrocytes in culture to study gene expression and function of 5-HT2B receptors. The urease-treated mice showed depressive behaviour. Both mRNA and protein of 5-HT2B receptors were increased in the brains of urease-treated mice and in ammonium-treated cultured astrocytes. Further study revealed that mRNA and protein expression of adenosine deaminase acting on RNA 2 (ADAR2), an enzyme catalyze RNA deamination of adenosine to inosine was increased in the brains of urease-treated mice and in ammonium-treated cultured astrocytes. This increase in ADAR2 induced RNA editing of 5-HT2B receptors. Cultured astrocytes treated with ammonium lost 5-HT induced Ca 2+ signalling and ERK1/2 phosphorylation, indicating dysfunction of 5-HT2B receptors. This is in agreement with our previous observation that edited 5-HT2B receptors no longer respond to 5-HT (Hertz et al., 2014). Ammonium effects are inhibited by ADAR2 siRNA in cultured astrocytes, suggesting that increased gene expression and editing and loss of function of 5-HT2B receptors are results of increased activity of ADAR2. In summary, we have demonstrated that functional malfunction of astrocytic 5-HT2B receptors occurs in animal models of major depression, Parkinson depression and hepatic encephalopathy albeit via different mechanisms. Understanding the role of astrocytic 5-HT2B receptors in different pathological contexts may instigate development of novel therapeutic strategies for treating disease-specific depressive behaviour. Highlights: Increase of astrocytic ADAR2 gene expression, 5-HT2B R RNA editing and disfunction by ammonium.